Review: Pengaruh Faktor Risiko Terhadap Induksi Persalinan: Review: The Effect of Risk Factors on Induction of Labor - Esmaya R. A. Adaniyah; Endang Sawitri; Erwin Ginting (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Abstract Induction of labor has become one of the most common interventions in modern obstetrics, with an increasing number of pregnant women worldwide that received labor induction interventions to deliver their babies. Labor induction was influenced by several risk factors. This systematic review study aimed to evaluate the influence of risk factors against induction of labor. Searches were performed by searching articles using electronic databases or search engine i.e Pubmed, Clinical Key, Google Scholar, Research Gate, or Science Direct that were limited to studies published between 2015 and 2020 in English and Indonesian Language. 270 studies was found and 48 studies were selected based on the inclusion criteria. The results of this systematic reviews showed that maternal age was not affecting labor induction in 71.1% of the studies evaluated, parity was affecting labor induction in 90% of the studies, body mass index was affecting labor induction in 66.7% of the studies, and Bishop Score was affecting labor induction in 90.3% of the studies. It can be concluded that maternal age was not affecting induction of labor, but labor induction were influenced by parity, body mass index and Bishop score in the majority of the included studies. Abstrak Induksi persalinan telah menjadi salah satu intervensi yang paling umum dalam kebidanan modern, dimana semakin banyak wanita hamil di seluruh dunia yang menerima intervensi induksi persalinan untuk melahirkan bayi mereka. Induksi persalinan dipengaruhi oleh beberapa faktor risiko. Systematic review ini bertujuan untuk mengevaluasi bagaimana pengaruh faktor risiko terhadap induksi persalinan. Systematic review ini dilakukan dengan pencarian studi pada database atau search engine yang dapat diakses seperti Pubmed, Clinical Key, Google Scholar, Research Gate, atau Science Direct, dan dibatasi terbitan tahun 2015-2020 dalam Bahasa Indonesia dan Bahasa Inggris. Hasil pencarian diperoleh sebanyak 270 studi dan tersisa 48 studi yang memenuhi kriteria inklusi. Hasil penelitian menunjukkan usia maternal tidak mempengaruhi induksi persalinan pada 71,1% hasil studi, jumlah paritas mempengaruhi induksi persalinan pada 90 % hasil studi, indeks massa tubuh mempengaruhi induksi persalinan pada 66,7% hasil studi, dan skor Bishop mempengaruhi induksi persalinan pada 90,3% hasil studi. Disimpulkan bahwa usia maternal tidak mempengaruhi induksi persalinan, tetapi jumlah paritas, indeks massa tubuh dan skor Bishop mempengaruhi induksi persalinan pada sebagian besar studi yang diinklusi